Adhesive resin composition-coated electromagnetic steel sheet and method for producing same
By crystallizing part of the curing agent in the film of the adhesive resin composition and controlling the conditions of the heating and drying process, the problem of slow bonding and curing speed of the adhesive resin composition coated electromagnetic steel plate during long storage is solved, and efficient production of the iron core is achieved.
Patent Information
- Application Number
- CN202380056580.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-26
- Filing Date
- 2023-07-26
- Publication Date
- 2025-03-11
AI Technical Summary
The bonding resin composition coated electromagnetic steel plate is prone to bonding and degradation of bonding performance during long storage, and the curing speed is too slow during hot pressing, which affects the productivity of the iron core.
By crystallizing part of the curing agent in the film of the adhesive resin composition, the curing agent area ratio in the crystallization state is controlled to be between 0.10 and 40%, and the heating temperature and time are controlled in the heating and drying and curing process to ensure that the curing agent remains in the crystallization state and inhibit the slow curing reaction.
The bonding and bonding performance of the bonding resin composition coated electromagnetic steel sheet during long storage is effectively prevented, and short-term curing is achieved during hot pressing, thereby improving the productivity of the iron core.
Smart Images

Figure BDA0005257811260000151 
Figure BDA0005257811260000271 
Figure BDA0005257811260000281
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive resin composition-coated electromagnetic steel sheet and a method for producing the same. Background Art
[0002] The iron core used in motors and the like is assembled by punching and shearing electromagnetic steel sheets into a predetermined shape, and then stacking and fixing them. As a fixing method, the following method is known: a method that can fix without causing processing strain or thermal strain, and can insulate the stacked steel sheets to increase eddy current resistance and reduce iron loss, and a method that fixes with a thermosetting adhesive that is also excellent in heat resistance under actual use environments.
[0003] The method of stacking and fixing the electromagnetic steel sheets with a thermosetting adhesive is generally to punch and shear the electromagnetic steel sheets and then stack and heat press them. In addition, the method of applying the thermosetting adhesive on the surface of the electromagnetic steel sheets can be roughly divided into two types according to the timing of applying the thermosetting adhesive.
[0004] One is a method of applying a thermosetting adhesive to the electromagnetic steel sheet after the punching process. This method is further divided into a method of spraying a thermosetting adhesive onto the surface of the electromagnetic steel sheet before the shearing process, and then shearing and laminating; and a method of immersing the laminated iron core in an adhesive liquid and allowing it to penetrate between the laminated electromagnetic steel sheets after the punching, shearing and lamination are completed.
[0005] Another method is to apply a thermosetting adhesive to at least one surface of the electromagnetic steel sheet in advance and dry it, and then perform a lamination after punching and shearing. Hereinafter, an electromagnetic steel sheet having an adhesive resin composition coating in which a thermosetting adhesive is applied to at least one surface of the electromagnetic steel sheet and dried is sometimes referred to as an "adhesive resin composition coated electromagnetic steel sheet".
[0006] Among the methods of stacking and fixing these electromagnetic steel sheets, the latter is also excellent in terms of workability, uniformity, productivity, etc. of adhesive coating, and has therefore attracted attention in recent years.
[0007] In the latter method, first, an adhesive resin composition coated electromagnetic steel sheet (semi-finished product) having an adhesive resin composition film in a semi-cured state in which the curing reaction of the thermosetting adhesive applied to the surface of the electromagnetic steel sheet is stopped midway is obtained. Then, an iron core (finished product) is manufactured using it. The adhesive resin composition coated electromagnetic steel sheet is manufactured by applying a thermosetting adhesive based on a mixture of a thermosetting adhesive resin and a curing agent to the surface of a wide electromagnetic steel sheet and heating it. The manufactured adhesive resin composition coated electromagnetic steel sheet is wound up and stored in the form of a steel coil. In addition, the adhesive resin composition coated electromagnetic steel sheet is sometimes unwound from the steel coil, cut into a blanking width, and then wound up again in the form of a steel coil and stored again.
[0008] The iron core is manufactured by punching, shearing, laminating and thermocompression bonding electromagnetic steel sheets coated with an adhesive resin composition. Therefore, not only is a technology required to uniformly coat the surface of the steel sheet with an adhesive resin composition film, but also a technology is required to prevent defects such as poor separation between the steel sheets when the steel sheets are coiled or uncoiled, and insufficient bonding strength after thermocompression bonding.
[0009] It should be noted in particular that the process from the application of the thermosetting adhesive when manufacturing the adhesive resin composition coated electromagnetic steel sheet to the hot pressing when manufacturing the iron core is usually not continuous. Therefore, the manufacturing process of the adhesive resin composition coated electromagnetic steel sheet (semi-finished product) includes the process of storage and transportation from the end of drying to the start of punching. In addition, the storage period may sometimes be a very long period of more than several months. In addition, there are cases where the steel plate is stored in a cabin that may become a high temperature and high humidity environment of about 50°C for several weeks during transportation. During this storage period, the adhesive resin composition film of the adhesive resin composition coated electromagnetic steel sheet is in a semi-cured state (non-equilibrium state) in which the curing reaction, which is an irreversible reaction, is stopped halfway.
[0010] Therefore, the adhesive resin composition coated electromagnetic steel sheet is very unstable. Therefore, after the adhesive is applied and dried, when it is stored for a long time in a high temperature and high humidity environment, the following defects (A) and (B) are likely to occur. In addition, the so-called high temperature and high humidity environment is, for example, an environment in a ship warehouse sailing near the equator, where the storage temperature is about 50°C.
[0011] (A) Adhesion: The curing reaction of the adhesive resin proceeds between the surfaces of the adhesive resin composition film during storage, and the stacked and stored steel plates are adhesively bonded.
[0012] (B) Reduction in bonding performance: The curing of the adhesive resin composition film is excessive during storage. As a result, even if it is heated for thermocompression bonding, the adhesive resin cannot be fully softened, and the adhesive resin cannot penetrate into the unevenness of the adherend surface, so it cannot exert an anchoring effect, and the bonding performance between the laminated steel plates is reduced.
[0013] Therefore, a technology for controlling the curing state of the adhesive resin to solve the instability is disclosed. Patent document 1 discloses a technology for covering the electromagnetic steel sheet with an adhesive resin having a Tg (glass transition temperature) or a softening temperature of 60°C or more. By vitrifying the adhesive resin at room temperature, it is possible to prevent the surface of the adhesive layer from becoming sticky and prevent adhesion. This technology is effective in manufacturing an iron core by drying the electromagnetic steel sheet coated with the adhesive resin composition and then performing punching and hot pressing.
[0014] In addition, patent documents 2 to 4 disclose technologies for suppressing the curing reaction at room temperature by using a latent curing agent as a curing agent for a thermosetting resin. Here, the so-called latent curing agent is, for example, a curing agent that imparts latency to a curing agent as explained in non-patent document 1. The latent property of the curing agent can suppress the reaction at room temperature, and the curing reaction of the thermosetting resin can be rapidly carried out by applying external stimuli such as heat, light, moisture, and pressure.
[0015] Furthermore, Patent Documents 5 and 6 teach that sticking during storage can be prevented by coating an electromagnetic steel sheet with an adhesive resin cured with a latent curing agent.
[0016] Prior art literature
[0017] Patent Literature
[0018] Patent Document 1: Japanese Patent Application Publication No. 2002-260910
[0019] Patent Document 2: Japanese Patent Application Publication No. 2020-100727
[0020] Patent Document 3: Japanese Patent Application Publication No. 2017-031268
[0021] Patent Document 4: Japanese Patent Application Publication No. 2014-152236
[0022] Patent Document 5: Japanese Patent Application Publication No. 6-182296
[0023] Patent Document 6: Japanese Patent Application Publication No. 11-162724
[0024] Non-patent document 1: Journal of the Japanese Society of Adhesion, vol.53, No.4 (2017), pp.122-128 Summary of the invention
[0025] Technical problem to be solved by the invention
[0026] However, Patent Document 1 does not disclose a method for suppressing the curing reaction during storage of an adhesive resin composition coated electromagnetic steel sheet. In the method of Patent Document 1, blocking due to bonding may occur in general production of an adhesive resin composition coated steel sheet accompanied by long-term storage, and there is also a case where the bonding energy is reduced during thermocompression bonding.
[0027] Although Patent Documents 2 to 4 disclose technologies for suppressing the reaction between the resin and the curing agent in the liquid adhesive before being applied to the steel plate and maintaining the viscosity that facilitates application during the storage of the adhesive (stable storage of the liquid adhesive and prolonged pot life), there is no disclosure related to the stability of the adhesive resin of the adhesive resin composition coated electromagnetic steel sheet after undergoing a heating process based on drying.
[0028] Patent Documents 5 to 6 do not disclose the state of the latent curing agent in the adhesive resin after heat drying. It is common that the curing agent heated once in the drying process changes state and loses its latency. Therefore, if the state of the latent curing agent in the adhesive resin composition film after drying is not controlled, it is difficult to suppress the progress of the curing reaction during storage, and there is a possibility of adhesion and reduction of bonding performance due to adhesion.
[0029] Furthermore, according to the time-temperature conversion rule related to the reaction activation energy and viscoelasticity of the curing agent and the estimated result of the reaction activation energy of the curing agent, the diffusion of the curing agent into the adhesive resin and the reaction with the adhesive resin that occur at room temperature for several months correspond to about a few minutes at the curing temperature in most cases. Therefore, if the diffusion rate of the curing agent into the adhesive resin or the reaction rate with the adhesive resin in the adhesive resin composition film of the adhesive resin composition-coated electromagnetic steel sheet is reduced, the curing rate in the hot pressing process when the iron core is manufactured using the adhesive resin composition is also reduced, and the productivity of the iron core may be reduced.
[0030] As mentioned above, usually, the manufacturing process from the application of the thermosetting adhesive when manufacturing the adhesive resin composition coated electromagnetic steel sheet (semi-finished product) to the hot pressing when manufacturing the iron core (finished product) is not continuous. Therefore, after the adhesive resin composition coated electromagnetic steel sheet is obtained (after the drying of the adhesive is completed) to the start of the punching process, the adhesive resin composition film is stored in a semi-cured (non-equilibrium) state in which the curing reaction, which is an irreversible reaction, is stopped midway. As a result, the technical problem is to prevent adhesion and reduction of bonding energy during storage (especially during long-term storage). In addition, in the hot pressing process when using the adhesive resin composition coated electromagnetic steel sheet to manufacture the iron core, it is also necessary to be able to cure in a short time so that the iron core can be produced efficiently.
[0031] The present invention is made in view of such circumstances, and an object of the present invention is to provide an adhesive resin composition-coated electromagnetic steel sheet which can prevent adhesion and reduction in adhesive performance even if stored for a long period of time after adhesive coating and drying, and in which the adhesive resin composition film can be cured in a short time in the hot pressing step when manufacturing the iron core.
[0032] Technical means for solving technical problems
[0033] The present invention has been made to solve the above-mentioned technical problems, and is aimed at the following adhesive resin composition-coated electromagnetic steel sheet and a method for producing the same.
[0034] (1) An adhesive resin composition coated electromagnetic steel sheet comprising a steel sheet and an adhesive resin composition coating film on at least one surface of the steel sheet,
[0035] The adhesive resin composition film is a semi-cured product of an adhesive resin composition composed of a curing agent and an adhesive resin at least part of which contains a thermosetting resin.
[0036] The maximum needle penetration λ of the adhesive resin composition film at 100 to 300° C. measured by thermomechanical analysis described in JIS K 7196:2012 is 3% or more and less than 100%,
[0037] A part of the curing agent is present in the adhesive resin composition film in a crystalline state.
[0038] The area ratio of the curing agent in a crystalline state in the cross section of the adhesive resin composition film parallel to the surface of the steel plate is 0.10 to 40%.
[0039] (2) An electromagnetic steel sheet coated with the adhesive resin composition according to (1) above,
[0040] The area ratio of the crystalline curing agent is 0.70 to 20%.
[0041] (3) The adhesive resin composition coated electromagnetic steel sheet as described in (1) or (2) above,
[0042] The adhesive resin composition film has a softening start temperature Tss of 50° C. or higher as measured by thermomechanical analysis according to JIS K 7196:2012, and a maximum penetration λ of 15% or higher at 100 to 300° C.
[0043] (4) The adhesive resin composition coated electromagnetic steel sheet according to any one of (1) to (3) above,
[0044] The thermosetting resin includes one or more selected from epoxy resin, acrylic resin, urethane resin and unsaturated polyester resin.
[0045] (5) The adhesive resin composition coated electromagnetic steel sheet according to any one of (1) to (4) above,
[0046] The curing agent includes one or more selected from amine curing agents, amide curing agents, and imidazole curing agents.
[0047] (6) A method for producing an adhesive resin composition coated electromagnetic steel sheet, which is the method for producing an adhesive resin composition coated electromagnetic steel sheet according to any one of (1) to (4) above, comprising:
[0048] A coating step of coating a liquid thermosetting adhesive including the adhesive resin and the curing agent on at least one surface of the steel plate; and
[0049] The steel plate coated with the thermosetting adhesive is heated and then cooled to form a coating of the adhesive resin composition on the surface of the steel plate by heating and drying.
[0050] The heating temperature in the heating drying and curing step is a temperature T in the temperature range of 100 to 250° C.
[0051] The heating time in the heating drying and curing step satisfies the following formula (i).
[0052] 0.8≦t / t0≦18.0···(i)
[0053] In addition, the meanings of the symbols in the above formula (i) are as follows.
[0054] t: Heating time in the heating, drying and curing process
[0055] t0: time required to form an adhesive resin composition film having a softening start temperature of 50° C. when the thermosetting adhesive is dried at the temperature T
[0056] (7) The method for producing an adhesive resin composition-coated electromagnetic steel sheet according to (6) above,
[0057] The glass transition temperature Tg of the adhesive resin uc Above 30℃,
[0058] The heating temperature in the heating drying and curing step is a temperature T in the temperature range of 100 to 190° C.
[0059] The heating time in the heating drying and curing step satisfies the following formula (ii).
[0060] 1.3≦t / t0≦15.0···(ii)
[0061] The meanings of the symbols in the above formula (ii) are as follows:
[0062] t: Heating time in the heating, drying and curing process
[0063] t0: time required to form an adhesive resin composition film having a softening start temperature of 50° C. when the thermosetting adhesive is dried at the temperature T.
[0064] (8) The method for producing an adhesive resin composition-coated electromagnetic steel sheet according to (6) or (7),
[0065] The adhesive resin contains 50% by mass or more of one or more thermosetting resins selected from epoxy resins, acrylic resins, urethane resins, and unsaturated polyester resins, based on the total amount of the adhesive resin.
[0066] (9) The method for producing an adhesive resin composition-coated electromagnetic steel sheet according to any one of (6) to (8) above,
[0067] The curing agent includes at least one selected from an amine curing agent, an amide curing agent, and an imidazole curing agent.
[0068] Effects of the Invention
[0069] According to the present invention, an adhesive resin composition coated electrical steel sheet is obtained which can prevent adhesion and adhesive performance degradation even if stored for a long time after adhesive application and drying, and can cure the adhesive resin composition film in a short time during thermocompression bonding. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 This is a diagram for explaining the analysis method of the softening start temperature Tss and the maximum needle penetration λ of the adhesive resin composition film.
[0071] Figure 2 This is a polarizing microscope image of a cross section of the adhesive resin composition film of the adhesive resin composition-coated electrical steel sheet of Example 1, parallel to the surface of the steel sheet.
[0072] Figure 3 This is a polarizing microscope image of a cross section of the adhesive resin composition film of the adhesive resin composition-coated electrical steel sheet of Example 2, parallel to the surface of the steel sheet.
[0073] Figure 4 This is a polarizing microscope image of a cross section of the adhesive resin composition film of the adhesive resin composition-coated electrical steel sheet of Example 5, parallel to the surface of the steel sheet.
[0074] Figure 5 This is a polarizing microscope image of a cross section of the adhesive resin composition film of the adhesive resin composition-coated electrical steel sheet of Example 6, parallel to the surface of the steel sheet.
[0075] Figure 6 This is a polarizing microscope image of a cross section of the adhesive resin composition film of the adhesive resin composition-coated electrical steel sheet of Example 7, parallel to the surface of the steel sheet.
[0076] Figure 7 This is a polarizing microscope image of a cross section of the adhesive resin composition film of the adhesive resin composition-coated electrical steel sheet of Example 11, parallel to the surface of the steel sheet.
[0077] Figure 8 This is a polarizing microscope image of a cross section of the adhesive resin composition film of the adhesive resin composition-coated electrical steel sheet of Example 12, parallel to the surface of the steel sheet.
[0078] Fig. 9This is a polarizing microscope image of a cross section of the adhesive resin composition film of the adhesive resin composition-coated electrical steel sheet of Comparative Example 2, parallel to the surface of the steel sheet.
[0079] Fig.10 This is a polarizing microscope image of a cross section of the adhesive resin composition coating of the adhesive resin composition-coated electrical steel sheet of Comparative Example 3, parallel to the surface of the steel sheet. DETAILED DESCRIPTION
[0080] The following describes the details of the present invention in the order of the focus, the specific implementation method based on the focus, and the method of use. The description of the constituent elements recorded below is an example (representative example) of the implementation method of the present invention, and the present invention is not limited to the following content without changing its purpose.
[0081] <Point of view of the present invention>
[0082] (Control Policy)
[0083] The inventors of the present invention conducted the following studies in order to solve the above-mentioned technical problems.
[0084] When the adhesive resin composition coated steel plate is stored for a long time (for example, several months) in a high temperature and humid environment, the curing agent diffuses into the adhesive resin in the adhesive resin composition film, and a slow curing reaction (hereinafter referred to as "slow curing reaction") is carried out in the adhesive resin composition film. Therefore, if the slow curing reaction in the adhesive resin composition film during storage is not suppressed, it is difficult to prevent the occurrence of adhesive adhesion and the reduction of bonding performance caused by over-curing of the adhesive resin composition film. On the other hand, if the reaction rate of the curing reaction of the adhesive resin composition film is too slow, the curing reaction will not be carried out in a short time during hot pressing. As a result, the productivity of the iron core is reduced.
[0085] Therefore, the inventors of the present invention have focused on the following points and conducted studies in order to prevent adhesion blocking and reduction in adhesive performance during storage.
[0086] 1) Basic process of slow curing reaction
[0087] First, when the slow curing reaction in the adhesive resin composition film during storage of the adhesive resin composition coated electrical steel sheet is decomposed into the basic processes, it can be divided into the following three processes.
[0088] (a) Dissolution of curing agent
[0089] (b) Diffusion of curing agent into adhesive resin
[0090] (c) Conflict and reaction between curing agent and adhesive resin molecules
[0091] Therefore, in order to suppress the slow curing reaction in the adhesive resin composition film during storage of the adhesive resin composition-coated electrical steel sheet, it is necessary to reduce any one of the dissolution rate, diffusion rate, and reaction activity of the curing agent.
[0092] In the present invention, the dissolution of the curing agent (a) is suppressed to suppress the slow curing reaction in view of the following aspects. Specifically, a curing agent that at least partially crystallizes at room temperature is used, and a certain amount of the curing agent in a crystalline state (hereinafter, sometimes referred to as "curing agent crystals") is allowed to remain in the adhesive resin composition film to suppress the slow curing reaction.
[0093] First, focusing on (b) and (c), the disadvantages of suppressing the slow curing reaction are as follows.
[0094] In order to inhibit the diffusion of the curing agent of (b) to the adhesive resin and the conflict and reaction between the curing agent of (c) and the adhesive resin molecules to inhibit the slow curing reaction in the adhesive resin composition film, it is necessary to suppress the thermal mobility of the adhesive resin phase molecules and increase the activation energy of the curing reaction at room temperature. However, in the former case, the crystallization temperature or glass transition temperature (Tg) of the adhesive resin must be increased. As a result, the diffusion of the curing agent during hot pressing is also slowed down, and hot pressing at a higher temperature is required. In addition, in the latter case, in most cases, the curing reaction rate of the adhesive resin composition film during hot pressing is also slowed down, which damages the productivity of the iron core.
[0095] On the other hand, focusing on (a), the advantage of allowing a certain amount of curing agent to remain in a crystalline state is as follows.
[0096] The dissolution of the curing agent (a) can be controlled by the state change of the curing agent, and the state change of crystallization and dissolution of the curing agent is thermodynamically reversible. Therefore, if it is appropriately heated and cooled during the heat drying and curing, even if the crystals are dissolved by heating, the crystals can be precipitated. In addition, the crystallized curing agent will not dissolve at room temperature and can stably exist in the adhesive resin composition film. Therefore, if a certain amount of curing agent is left in a crystalline state in the adhesive resin composition film covering the electromagnetic steel sheet, the slow curing reaction can be stably suppressed. In addition, with respect to solubility, the thermal mobility and reactivity of the adhesive resin phase molecules can be controlled separately. Therefore, even if they are controlled as described above for short-time curing in the hot pressing process, the slow curing reaction can be stably suppressed during storage.
[0097] Next, a specific implementation method will be described.
[0098] <Adhesive resin composition coated electrical steel sheet>
[0099] The present invention relates to an adhesive resin composition coated electromagnetic steel sheet (hereinafter, sometimes described as "the adhesive resin composition coated electromagnetic steel sheet of the present invention"), which is an adhesive resin composition coated electromagnetic steel sheet having a steel sheet and an adhesive resin composition film on at least one surface of the steel sheet, wherein the adhesive resin composition film is a semi-cured product of an adhesive resin composition composed of a curing agent and an adhesive resin at least part of which contains a thermosetting resin, and the maximum needle penetration λ of the adhesive resin composition film at 100 to 300° C. measured by thermomechanical analysis described in JIS K 7196:2012 is 3% or more and less than 100%, a part of the curing agent is present in a crystalline state in the adhesive resin composition film, and the area ratio of the crystalline curing agent in a cross section of the adhesive resin composition film parallel to the surface of the steel sheet is 0.10 to 40%.
[0100] By adopting such a structure, the following effects can be obtained during storage of the adhesive resin composition coated electrical steel sheet of the present invention and in each step during thermocompression bonding.
[0101] The following effects are obtained during storage.
[0102] Prevent degradation of bonding performance and adhesion:
[0103] A certain amount of curing agent is present in the adhesive resin composition film in a crystalline state that is difficult to dissolve in the adhesive resin, so that during the storage period of the adhesive resin composition coated electromagnetic steel sheet, the curing agent can be suppressed from dissolving in the adhesive resin. As a result, it is possible to suppress the diffusion and migration of the curing agent in the adhesive resin composition film, at the interface between the adhesive resin composition film and the steel sheet, and at the interface between the adhesive resin composition films when the adhesive resin composition coated electromagnetic steel sheets are overlapped when being wound in a steel coil. In this way, the slow curing reaction in the adhesive resin composition film during storage and the reaction between the adhesive resin composition film and the adherend can be suppressed, and the reduction of bonding performance and bonding adhesion can be prevented.
[0104] In the thermocompression bonding process, the following effects are obtained.
[0105] ·Short-time curing of adhesive resin composition film during thermocompression bonding:
[0106] By dissolving the curing agent remaining in a crystalline state during storage during hot pressing, diffusion into the adhesive resin is promoted, and the adhesive resin composition film can be cured in a short time. In addition, by setting it to a crystalline state, the dissolution of the curing agent is suppressed, thereby suppressing the slow curing reaction in the adhesive resin composition film during storage. Therefore, a catalyst and / or accelerator that promotes the activation energy of the reaction can also be used in combination, and these can be added to allow the short-term curing of the adhesive resin composition film during hot pressing and the suppression of the slow curing reaction in the adhesive resin composition film during the storage period of the adhesive resin composition-coated electromagnetic steel sheet.
[0107] It should be noted that the use of a catalyst and / or promoter that increases the activation energy of the reaction is not essential.
[0108] [Steel Plate]
[0109] The steel sheet other than the adhesive resin composition film in the adhesive resin composition-coated electromagnetic steel sheet of the present invention (sometimes referred to as "electromagnetic steel sheet") is not particularly limited, and any known steel sheet can be used.
[0110] [Adhesive resin composition film]
[0111] The adhesive resin composition film is a layer formed on at least one surface of the steel plate, and is a semi-cured adhesive resin composition composed of an adhesive resin and a curing agent. The adhesive resin composition film composed of a semi-cured thermosetting adhesive resin composition is a material that can exhibit adhesive properties by heating and pressurizing, so by stacking the adhesive resin composition coated electromagnetic steel sheets and thermally pressing them, the adhesive resin composition coated electromagnetic steel sheets can be bonded to each other.
[0112] [Adhesive resin composition]
[0113] The adhesive resin composition is composed of an adhesive resin at least part of which contains a thermosetting resin and a curing agent. The adhesive resin composition in the adhesive resin composition film is in a semi-cured state in which curing has progressed locally.
[0114] [Adhesive resin]
[0115] Since the adhesive resin exerts thermosetting properties, at least a part of it contains a thermosetting resin. As mentioned above, the adhesive resin composition is composed of an adhesive resin at least a part of which contains a thermosetting resin and a curing agent. Therefore, the adhesive resin refers to a component from which the curing agent (unreacted curing agent) is removed from the adhesive resin composition. The thermosetting resin is a resin that is cross-linked and cured by three-dimensional polymers by heating during use and applying a catalyst depending on the situation. In the adhesive resin composition film, a part of the thermosetting resin undergoes a cross-linking reaction with the curing agent, and the remaining part exists in an unreacted state.
[0116] [Curing agent]
[0117] The curing agent contained in the adhesive resin composition is a compound that reacts with the functional groups contained in the thermosetting resin to form a three-dimensional structure, so that the adhesive resin composition is cured, and at least a part of it crystallizes at room temperature. That is, a part of the curing agent is present in the adhesive resin composition film in a crystalline state. The curing agent used in the present invention can crystallize at room temperature. In the adhesive resin composition film, it is sufficient to contain a curing agent that can exist in a crystalline state. Only a curing agent that can crystallize at room temperature can be used, or a curing agent that can crystallize at room temperature and a curing agent that does not crystallize at room temperature can be used in combination. In addition, the curing agent in the adhesive resin composition film refers to an unreacted curing agent component that does not react with the thermosetting resin.
[0118] [Semi-cured material]
[0119] The adhesive resin composition forming the adhesive resin composition film is a semi-cured product in which curing is partially carried out. The so-called semi-cured product is a material in which the curing of the adhesive resin composition has not been carried out to 100%. In the present invention, whether it is a semi-cured state is judged by the maximum penetration described later as an index. Specifically, if the maximum penetration measured by the thermomechanical analysis described in JIS K 7196:2012 is 3% or more and less than 100%, it is judged to be a semi-cured state.
[0120] [Amount of the crystalline curing agent in the adhesive resin composition film]
[0121] The adhesive resin composition coated electromagnetic steel sheet of the present invention contains a certain amount of a crystalline curing agent (curing agent crystals) in the adhesive resin composition film. The amount of curing agent crystals in the adhesive resin composition film can be measured by using the area ratio of the crystalline curing agent in the cross section of the adhesive resin composition film parallel to the surface of the steel plate as an indicator. In the adhesive resin composition coated electromagnetic steel sheet of the present invention, the area ratio of the crystalline curing agent in the cross section of the adhesive resin composition film parallel to the surface of the steel plate (hereinafter sometimes described as "area ratio of curing agent crystals") is 0.10 to 40%. In addition, the area ratio of the curing agent crystals is measured and quantified by the method described later.
[0122] When the area ratio of the curing agent crystals is less than 0.10%, the following two situations are considered, but neither of them can reflect the desired performance. One is that the content of the curing agent itself is insufficient, and the other is that after the drying is completed, the curing agent is almost dissolved in the adhesive resin, and there is no residual crystalline curing agent. In the former case, it is difficult to ensure the bonding strength and heat resistance after hot pressing. In the latter case, the diffusion and reaction of the curing agent proceed during storage, causing adhesion, or excessive curing has occurred, resulting in loss of bonding energy during hot pressing.
[0123] In addition, the area ratio of the curing agent crystal is set to 0.10% or more for the following reasons. When a curing agent with a fast dissolution rate is used, there is a situation where the curing agent crystals are almost dissolved due to the heating in the heat drying and curing process. However, if more than 0.10% remains after drying, the curing agent can be crystallized again using it as a core during storage. As a result, even a curing agent with a fast dissolution rate (such as DDS, etc.) can stably suppress the slow curing reaction. On the other hand, when the area ratio of the curing agent crystal is less than 0.10%, since there is no recrystallization nucleus, crystallization is not carried out, and the dissolved curing agent diffuses into the adhesive resin composition film, and the slow curing reaction is easy to proceed.
[0124] On the other hand, when the area ratio of the curing agent crystals is higher than 40%, the reaction rate of the curing reaction of the adhesive resin composition film is too slow, so the curing reaction will not proceed in a short time during hot pressing. In addition, during punching and shearing, stress is concentrated on the cross section of the adhesive resin phase and the curing agent crystals, destroying the adhesive resin composition film. Moreover, in the case where the curing agent is excessive relative to the adhesive resin, the area ratio of the curing agent crystals is also excessive, but in this case, a part of it may not react and remain in the adhesive resin composition film after hot pressing. Stress is concentrated in the interface between the remaining excess curing agent crystals and the adhesive resin, and the strength and toughness of the adhesive resin composition film may be reduced. In addition, when the core is heated during continuous operation, the curing agent crystals dissolve, the adhesive resin composition film can be plasticized, and the strength and heat resistance are reduced.
[0125] [Preferred range of area ratio of the curing agent in a crystalline state in a cross section of the adhesive resin composition film parallel to the surface of the steel plate]
[0126] The preferred area ratio of the curing agent crystals is 0.50 to 30%. By setting it to 0.50% or more, most of the curing agent is suppressed from dissolving and diffusing, and the slow reaction during storage can be further suppressed. By setting it to 30% or less, the strength and toughness reduction caused by the remaining curing agent can be further prevented. More preferably, it is 0.50 to 25%, and more preferably 0.70 to 20% for the same reason.
[0127] [Method for Quantifying the Area Ratio of the Crystalline Curing Agent in the Cross Section of the Adhesive Resin Composition Film Parallel to the Surface of the Steel Plate]
[0128] The curing agent crystals have optical anisotropy, so they become bright when observed through a polarizing filter configured in an orthogonal Nikkor. On the other hand, the adhesive resin is optically isotropic and therefore becomes dark. Therefore, by using this difference, it is possible to distinguish between the adhesive resin phase mainly composed of the adhesive resin and the curing agent crystals other than the curing agent crystals. Specifically, the adhesive resin composition film covering the steel plate is observed by a polarizing microscope in a cross section parallel to the surface of the steel plate. More specifically, as a polarizing microscope, a microscope manufactured by OLYMPUS: BX53M or an upright microscope LV150N manufactured by NIKON can be cited.
[0129] Furthermore, a polarizing filter (for example, U-AN360-3, U-POTP3, etc. manufactured by OLYMPUS) is set on an orthogonal Nicol and observed at 100 to 800 times. In addition, the magnification can be appropriately selected within this range according to the difficulty of identifying the crystalline image of the curing agent. Thereafter, color photography is performed, RGB tone segmentation is performed, and only the G component is extracted. In this way, binarization is performed using image processing software (for example, image processing software in VHX5000 manufactured by KEYENCE) to obtain the area ratio of the bright phase, so that the area ratio of the curing agent in the crystalline state in the cross section of the adhesive resin composition film parallel to the surface of the steel plate can be quantified. In addition, the area ratio is set as the average value of the values measured and quantified in more than 3 fields of view selected arbitrarily.
[0130] [Softening start temperature Tss and maximum needle penetration λ]
[0131] The adhesive resin composition film preferably has a softening start temperature Tss of 50°C or higher as measured by a thermomechanical analyzer (TMA) in a penetration mode according to JIS K 7196: 2012, and a maximum penetration λ of 15% or higher at 100 to 300°C. The adhesive resin composition film satisfying such a softening start temperature and maximum penetration λ is in a state where curing is properly progressed, and the following effects are obtained.
[0132] By setting the softening start temperature Tss to above 50°C, the adhesive resin composition coated electromagnetic steel sheet obtained can be prevented from sticking during storage, and the effect of suppressing sticking and suppressing the reduction of adhesive performance can be further improved. The upper limit of the softening start temperature Tss is not particularly limited, but is preferably below 100°C. When the softening start temperature Tss exceeds 100°C, since the adhesive resin composition film is hard even in a semi-cured state, the diffusion rate of the curing agent to the adhesive resin is slow during the hot pressing process, and it is sometimes difficult to cure in a short time. Alternatively, hot pressing at a high temperature higher than 250°C is required in the hot pressing process, so sometimes the heating and cooling time becomes longer, and productivity is reduced.
[0133] By setting the maximum penetration λ to 15% or more, excessive hardening of the adhesive resin composition film can be further prevented, and an adhesive resin composition film that can be more easily softened during thermocompression bonding can be formed.
[0134] In order to fully soften the adhesive resin composition film during thermocompression bonding, the maximum penetration λ is preferably 30% or more, more preferably 60% or more. In addition, when the maximum penetration λ is higher than 95%, the curing degree of the adhesive resin composition film is too low, the adhesive resin composition film is soft, and the adhesive resin composition may flow out during thermocompression bonding. Therefore, it is desirable to set the upper limit of the maximum penetration λ to 95% or less, more preferably 80% or less.
[0135] Therefore, the adhesive resin composition film preferably has a maximum penetration λ of 15 to 95% and a softening start temperature Tss of 50 to 100°C, more preferably a maximum penetration λ of 30 to 90% and a softening start temperature Tss of 50 to 100°C, and further preferably a maximum penetration λ of 60 to 80% and a softening start temperature Tss of 50 to 100°C.
[0136] Here, the softening start temperature Tss and the maximum penetration λ will be described. Figure 2 This is a diagram for explaining the analysis method of the softening start temperature Tss and the maximum needle penetration λ of the adhesive resin composition film. Figure 2 The TMA curve shown is a typical TMA curve of the adhesive resin composition film of the present invention. The TMA curve can be obtained by measuring the adhesive resin composition film covering the steel plate according to the method of JIS K 7196:2012. Figure 2 As shown, the softening start temperature Tss is defined in the TMA curve as the intersection of a line extending toward the high temperature side from a straight line portion at the low temperature side where the needle (indenter) starts to penetrate and a line extending toward the low temperature side from a tangent line at a portion where the needle penetration speed is the largest.
[0137] The maximum needle penetration λ is defined as the percentage of the value obtained by dividing the maximum needle penetration length (μm) by the thickness (μm) of the adhesive resin composition film ((maximum needle penetration length / thickness of the adhesive resin composition film)×100). Figure 1 As shown, the maximum value (μm) of the needle penetration length can be obtained from the TMA curve. In addition, the measurement is carried out in a 100% N2 atmosphere, the heating rate is 15°C / min, the pressure is set to 0.6 to 2.0 MPa, and the diameter of the front end of the pressure head is set to 0.5 to 1.0 mm. In addition, the thickness of the adhesive resin composition film can be measured by cutting a cross section of the adhesive resin composition coated electromagnetic steel sheet and observing it under a microscope.
[0138] [Glass transition temperature Tg of uncured adhesive resin]
[0139] When the adhesive resin is not cured, that is, the glass transition temperature Tg (Tg uc ) is preferably above 30°C. uc When the temperature is less than 30°C, according to the target softening start temperature of the adhesive resin composition film (glass transition temperature at the start of softening, Tss), in order to form an adhesive resin composition film with the target softening start temperature (for example, 50°C or above), a large amount of heat must be input during the heat drying and curing after the steel plate is coated with the adhesive, so that the thermosetting adhesive resin composition is cured to a considerable extent. For this reason, most of the curing agent needs to be dissolved by heating during the heat drying and curing, and diffused into the adhesive resin composition film, and it is difficult to allow a certain amount of curing agent to remain in the adhesive resin composition film in a crystalline state.
[0140] In addition, the Tg of the adhesive resin uc It is preferably 80°C or lower. uc When the temperature is higher than 80° C., the viscosity of the adhesive applied to the steel plate becomes too high, making it difficult to apply the adhesive uniformly.
[0141] In addition, the Tg of the adhesive resin uc The composition (ingredients and formulation) of the adhesive resin covering the steel plate can be determined by nuclear magnetic resonance or pyrolysis gas chromatography, and calculated by the following formula (Fox's formula).
[0142] [Number 1]
[0143]
[0144] Here, ω i is the mixing ratio (weight ratio) of component i, Tg i is the glass transition temperature or softening start temperature of the i component. i It can be obtained by a known Tg or softening start temperature measurement method using a differential scanning calorimeter (DSC) or a thermomechanical analyzer (TMA) in accordance with JIS K7121: 2012 or JIS K 7196: 2012. In addition, known values recorded in manufacturer's catalog documents such as https: / / www.nscm.nipponsteel.com / epoxy / ec.html (April 2022) can also be used.
[0145] In addition, since the curing agent is not substantially vitrified, the Tg of the adhesive resin uc The influence caused is small, so the Tg of the adhesive resin composition can also be measured uc , taking it as the Tg of the adhesive resinuc . Tg of the adhesive resin composition uc The composition (ingredients and formulation) of the adhesive resin composition can be determined by nuclear magnetic resonance or pyrolysis gas chromatography, and a measurement sample of the same composition is prepared and obtained using a differential scanning calorimeter (DSC) according to a method based on JIS K 7121:2012. The measurement sample can be prepared, for example, by the method described in the examples. Specifically, the adhesive resin composition is diluted with an appropriate solvent to prepare a liquid thermosetting adhesive. After the liquid thermosetting adhesive is cast on a glass plate, it is vacuum dried to prepare an extruded film. Using the prepared extruded film, the Tg (midpoint glass transition temperature) is measured by a method based on JIS K 7121:2012, and this is taken as the Tg of the adhesive resin composition. uc .
[0146] [Thermosetting resin]
[0147] Specific examples of thermosetting resins include cross-linked resins such as epoxy resins, thermosetting acrylic resins, urethane resins, unsaturated polyester resins, phenolic resins, melamine formaldehyde resins, urea resins, and thermosetting polyimide resins. In the present invention, these resins may be used alone or in combination of two or more.
[0148] [Epoxy resin]
[0149] Epoxy resin is a resin containing two or more epoxy groups. Two or more epoxy groups in the resin are cross-linked by a suitable curing agent to make it three-dimensional and cured. Examples of epoxy resins containing epoxy groups include bisphenol-based (bisphenol A type, bisphenol F type, bisphenol AD type), naphthalene-based, cyclopentadiene-based epoxy resins, and the like.
[0150] [Thermosetting acrylic resin]
[0151] Examples of thermosetting acrylic resins include copolymers of acrylic acid esters or methacrylates, acrylic acid monomers having reactive functional groups such as hydroxyl, amino, N-methylol, N-alkoxymethyl carboxylic acid, acryl, epoxy, etc. Specifically, examples include copolymers of one or more acrylic acid monomers having reactive functional groups such as acrylic acid methyl or methacrylate methyl, acrylic acid, methacrylic acid, acrylamide, N-methylol acrylamide, N-(methoxymethyl) acrylamide, propyl methacrylate, glycidyl acrylate, and glycidyl methacrylate. The thermosetting acrylic resin can be crosslinked by utilizing the self-reactivity of the reactive functional groups, or crosslinked by reacting the reactive functional groups with a curing agent such as an amine system, so as to be cured.
[0152] [Urethane resin]
[0153] Examples of urethane resins include resins composed of residues of polyfunctional isocyanate compounds and hydroxyl-containing compounds. Specifically, examples include aromatic polyisocyanates such as tolyl diisocyanate, diphenylmethane isocyanate, and polymethylene polyphenyl polyisocyanate, aliphatic polyisocyanates such as hexamethylene diisocyanate and xylene isocyanate, or mixtures thereof, and resins composed of residues of hydroxyl-containing compounds such as polyether polyols, polyester polyols, polyacrylate polyols, and polycarbonate polyols. Urethane resins are crosslinked and cured by reaction with curing agents such as isocyanate curing agents or polyol curing agents.
[0154] [Unsaturated polyester resin]
[0155] Examples of the unsaturated polyester resin include dehydrated condensates of compounds in which unsaturated dibasic acids such as maleic anhydride, fumaric acid, and itaconic acid or a part thereof are replaced with saturated dibasic acids such as phthalic anhydride, isophthalic acid, and terephthalic acid, and compounds in which diols such as ethylene glycol, diethylene glycol, and propylene glycol or a part thereof are replaced with polyols such as glycerol and pentaerythritol. The unsaturated polyester resin can be crosslinked and cured by reacting with a curing agent such as an isocyanate curing agent.
[0156] [Other thermosetting resins]
[0157] As phenolic resin, there are resins having two or more phenols (phenol, cresol, etc.) in the resin. For example, there are resins composed of residues of phenols and formaldehydes or aldehydes. Specifically, there are phenol novolac resins, cresol novolac resins, cresol naphthol formaldehyde condensation products, triphenylmethane type multifunctional phenyl resins, etc. In addition, there are phenol aralkyl resins. In addition, as melamine formaldehyde resins, there are alkyl etherified melamine formaldehyde resins and their substitution products, etc. In addition, as urea resins, there are ethylene urea resins, etc. As thermosetting polyimide resins, there are resins composed of residues of polyvalent carboxylic acid dianhydrides and diamine compounds, etc. Specifically, there are thermosetting polyimide resins such as maleimide polymers, bismaleimide polymers, aminobismaleimide polymers, and bismaleimide triazine polymers. These resins can also be cured by crosslinking reactions with curing agents.
[0158] [Preferred examples of thermosetting resin]
[0159] Among the above-mentioned thermosetting resins, the glass transition temperature Tg uc There are many options for setting the temperature to 30°C or above. The curing reaction at high temperature is rapid, and the dispersed state of the curing agent is easy to manufacture. Based on this, the thermosetting resin preferably contains one or more selected from the group consisting of epoxy resin, acrylic resin, urethane resin and unsaturated polyester resin. Among them, the thermosetting resin most preferably contains epoxy resin from the perspective of economy, versatility and operability.
[0160] [Preferred Examples of Adhesive Resin Contained in Thermosetting Adhesive]
[0161] The adhesive resin contains one or more thermosetting resins selected from the group consisting of epoxy resins, acrylic resins, urethane resins and unsaturated polyester resins, and the total content (total mass of these thermosetting resins / mass (total amount) of the adhesive resin × 100 (%)) is preferably 50% by mass or more. Adhesive resins containing less than 50% by mass of these thermosetting resins may not fully exert the characteristics of these thermosetting resins. In particular, from the perspective of economy, versatility and operability, it is most preferred to contain an epoxy resin of 50% by mass or more.
[0162] The adhesive resin may contain a thermosetting resin, and may be composed of a thermosetting resin or may contain organic or inorganic components other than the thermosetting resin. For example, it may contain a thermoplastic resin; an impact modifier such as core-shell rubber or natural rubber; a curing accelerator such as dimethyl urea, boron trifluoride, or triphenylphosphine; a modifier for a known epoxy resin; a reaction control agent (catalyst, etc.); a surfactant; a rust inhibitor; a lubricant; an antioxidant; a defoaming agent; a coloring pigment, etc.
[0163] [Examples of curing agents]
[0164] Specific examples of the curing agent include amine, amide, imidazole, anhydride, phenol, and catalyst-based curing agents. In the present invention, for example, a crystalline curing agent that crystallizes at room temperature can be selected from the following specific examples and used alone or in combination of two or more.
[0165] [Amine curing agent]
[0166] Examples of the amine-based curing agent include, but are not limited to, aliphatic amines, aromatic amines, and guanidine compounds.
[0167] [Aliphatic amines]
[0168] Examples of the aliphatic amine include, but are not limited to, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, m-xylene diamine, trimethylhexamethylene diamine, 2-methylpentamethylene diamine, isophorone diamine, 1,3-bisaminomethylcyclohexane, bis(4-aminocyclohexyl)methane, norbornene diamine, 1,2-diaminocyclohexane, benzamide, methylcyclohexylamine, and diazabicycloundecene.
[0169] [Aromatic amines]
[0170] Examples of the aromatic amine include, but are not limited to, diaminodiphenylmethane, m-phenylenediamine, diaminodiphenyl sulfone (DDS), diethyltoluenediamine, trimethylenebis(4-aminobenzoate), polytetramethylene oxide diparaaminobenzoate, methylaniline, and dimethylaniline.
[0171] [Guanidane compounds]
[0172] Examples of the guanidine compound include, but are not limited to, dicyandiamide (DICY, cyanoguanidine) and derivatives thereof, methylguanidine, ethylguanidine, propylguanidine, butylguanidine, dimethylguanidine, trimethylguanidine, phenylguanidine, diphenylguanidine, and toluylguanidine.
[0173] [Amide curing agent]
[0174] Examples of the amide curing agent include, but are not limited to, those obtained by adding an acid anhydride to an amine curing agent and hydrazide compounds.
[0175] [Hydrazide compounds]
[0176] Examples of the hydrazide compound include, but are not limited to, succinic acid dihydrazide, adipic acid dihydrazide, phthalic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, p-hydroxybenzoic acid hydrazide, salicylic acid hydrazide, phenylaminopropionic acid hydrazide, and maleic acid dihydrazide.
[0177] [Imidazole curing agent]
[0178] Examples of the imidazole curing agent include imidazole isocyanuric acid compounds, diamino-6-[2-(2-methyl-1-imidazolyl)ethyl]-1,3,5-triazine (2MZ-AZINE), 1-cyanoethyl-2-ethyl-4-methylimidazole (CEMI), 2-ethyl-4-methylimidazole, 2-undecylimidazole (CEMI), and the like. 11 Z) etc.
[0179] [Anhydride curing agent]
[0180] Examples of the acid anhydride curing agent include, but are not limited to, phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, maleic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylnadic anhydride, hexahydrophthalic anhydride, and methylhexahydrophthalic anhydride.
[0181] [Phenolic curing agent]
[0182] The phenolic curing agent is not limited to the following, but examples thereof include phenol novolac resin, cresol novolac resin, phenol aralkyl resin, cresol aralkyl resin, naphthol aralkyl resin, biphenyl-modified phenolic resin, biphenyl-modified phenolic aralkyl resin, dicyclopentadiene-modified phenolic resin, aminotriazine-modified phenolic resin, naphthol novolac resin, naphthol-phenol co-condensed novolac resin, naphthol-cresol co-condensed novolac resin, and acryl acrylic phenolic resin.
[0183] [Catalyst type curing agent]
[0184] The catalyst type curing agent is not limited to the following, but examples thereof include a cationic heat curing catalyst, a BF3-amine complex, and 1,8-diazabicyclo[5.4.0]undec-7-ene.
[0185] Because the curing reaction rate of the adhesive resin composition film is fast during hot pressing, the adhesive resin composition film can be cured in a short time relatively easily, so the curing agent preferably includes one or more crystalline curing agents selected from the group consisting of amine curing agents, amide curing agents and imidazole curing agents. Among them, because the temperature at which the curing reaction of the resin composition film is most easily carried out can be increased, it is preferred to include one or more crystalline curing agents selected from the group consisting of aromatic amines, guanidine compounds, amide curing agents and imidazole curing agents. By using such a curing agent, there is a difference between the temperature at which the adhesive resin composition coated electromagnetic steel sheet is stored and the heating temperature during hot pressing, so it is easy to control the heating rate during hot pressing. From the perspective of handling and versatility, the curing agent is most preferably selected from the group consisting of dicyandiamide (DICY), diaminodiphenyl sulfone (DDS) and diamino-6-[2-(2-methyl-1-imidazolyl)ethyl]-1,3,5-triazine (2MZ-AZINE).
[0186] In the adhesive resin composition film of the adhesive resin composition-coated electrical steel sheet of the present invention, the specific amount of curing agent may be present in a crystalline state, and the types of the adhesive resin and curing agent are not limited to the above examples.
[0187] [Thickness of Adhesive Resin Composition Coated Magnetic Steel Sheet]
[0188] The thickness of the adhesive resin composition coated electromagnetic steel sheet of the present invention can be set to, for example, 0.10 mm or more and 0.50 mm or less. In addition, this is only the thickness range of the commonly known adhesive resin composition coated electromagnetic steel sheet, and the present invention can also be applied to adhesive resin composition coated electromagnetic steel sheets outside this range.
[0189] [Thickness of Adhesive Resin Composition Film]
[0190] The film thickness of the adhesive resin composition film in the adhesive resin composition coated electromagnetic steel sheet of the present invention is not particularly limited, and can be set to 2 to 10 μm, for example. When it is less than 2 μm, it is difficult to fully penetrate into the surface unevenness of the adherend, and it is difficult to exhibit the anchoring effect. When it is higher than 10 μm, the volume ratio of the adhesive resin composition film in the laminated core becomes too large, and the magnetic properties of the laminated core are sometimes reduced.
[0191] <Manufacturing method>
[0192] The present invention provides a method for producing an adhesive resin composition coated electrical steel sheet that preferably uses an adhesive resin composition film and achieves both good barrier properties and sufficient adhesive properties. The method for producing an adhesive resin composition coated electrical steel sheet of the present invention is not limited to the method described below.
[0193] The manufacturing method of the adhesive resin composition coated electromagnetic steel sheet of the present invention can be set as a manufacturing method having the following steps: an adhesive coating step, applying a liquid thermosetting adhesive containing an adhesive resin and a curing agent on at least one surface of the steel plate; and a heating, drying and curing step, heating the steel plate coated with the thermosetting adhesive and then cooling it to form an adhesive resin composition film on the surface of the steel plate.
[0194] [Adhesive coating process]
[0195] The adhesive application step is a step of applying a liquid thermosetting adhesive including an adhesive resin and a curing agent to at least one surface of the steel plate.
[0196] [Thermosetting adhesive]
[0197] The thermosetting adhesive that can be used in the manufacture of the adhesive resin composition coated electromagnetic steel sheet is a liquid containing an adhesive resin and a curing agent. Depending on the components of the adhesive resin composition film (semi-cured product) to be formed, in addition to the thermosetting resin and the curing agent, it also contains a thermoplastic resin; an impact modifier such as core-shell rubber and natural rubber; a curing accelerator such as dimethyl urea, boron trifluoride, and triphenylphosphine; a modifier for a known epoxy resin; a reaction control agent (catalyst, etc.); a surfactant; a rust inhibitor; a lubricant; an antioxidant; a defoaming agent; a coloring pigment, etc.
[0198] Thermosetting adhesives can be used directly in the uncured state if the adhesive resin composition constituting the adhesive resin composition film is in a liquid state, but when it is not in a liquid state or when the viscosity needs to be adjusted, a solvent is added to set it as a liquid composition containing the adhesive resin composition and the solvent. As the solvent, aromatic hydrocarbon solvents such as benzene, toluene, and xylene; alicyclic hydrocarbon solvents such as cyclohexane; ketone solvents such as acetone, methyl ethyl ketone, cyclohexanone (anon), and tetrahydrofuran (THF); halogen solvents such as dichloromethane, dichloroethane, and chloroform can be used.
[0199] Thermosetting adhesives can be used in the form of a liquid composed of an adhesive resin composition (adhesive resin composition itself), a liquid obtained by diluting the adhesive resin composition with a solvent, a liquid obtained by dispersing the adhesive resin composition in a solvent in the form of an emulsion, etc. Thermosetting adhesives may be a single-liquid type in which an adhesive resin and a curing agent are mixed during the production stage of the thermosetting adhesive, or a two-liquid type in which the adhesive resin and the curing agent are stored separately and mixed before coating.
[0200] The viscosity of the thermosetting adhesive is preferably 100 to 1500 mPas. When the viscosity is less than 100 mPas, it is difficult to apply the adhesive resin composition to a predetermined film thickness. On the other hand, when the viscosity is higher than 1500 mPas, it is difficult to apply uniformly or apply in a short time, resulting in uneven thickness in the width and length directions, and further deteriorating productivity.
[0201] The adhesive resin composition constituting the adhesive resin composition film is as described above. From the viewpoint of versatility, cost and performance diversity, the thermosetting adhesive preferably contains an epoxy resin. In addition, the thermosetting adhesive preferably contains 50% by mass or more of a thermosetting resin, and more preferably contains 50% by mass or more of an epoxy resin. The curing agent preferably comprises one or more selected from the group consisting of an amine curing agent, an amide curing agent and an imidazole curing agent. For example, it is preferred to include one or more selected from the group consisting of an amine curing agent, an amide curing agent and an imidazole curing agent, and contain an epoxy resin of 50% or more. The ratio of the thermosetting resin to the curing agent can be appropriately adjusted according to the types of the thermosetting resin and the curing agent, but for example, the functional group equivalent of the curing agent can be set to 0.8 to 1.2 relative to the functional group equivalent of the thermosetting resin.
[0202] The thermosetting adhesive is preferably a dispersion in which at least a portion of the curing agent is dispersed, and the particle size of the curing agent crystals dispersed in the thermosetting adhesive is preferably 2 to 20 μm. When the particle size of the curing agent crystals is less than 2 μm, it is difficult to handle, and the curing agent is usually completely dissolved by heating during heat drying and curing. At this time, among the dissolved curing agents, the unreacted curing agent that has not reacted with the thermosetting resin due to heating is difficult to recrystallize even if it becomes an overcooled state during the cooling process after the heat drying and curing process, due to the absence of curing agent crystals as the core. Therefore, there is a situation where it is difficult to make a specified amount of curing agent remain in the adhesive resin composition film in a crystalline state. In addition, when it is higher than 20 μm, it is difficult to make the adhesive resin composition film into a thin film of less than 10 μm and form it on the surface of the steel plate.
[0203] (Adhesive coating method)
[0204] The specific coating method of the thermosetting adhesive is appropriately selected in accordance with the properties of the thermosetting adhesive and is not particularly limited. For example, the coating method may be a roll coating method, a gravure coater method, an air knife coater method, a blade coater method, a knife edge coating method, a rod coating method, a kiss coater method, a bead coating method, a coating caster method, a rotary screen method, a dip coating method in which the steel plate is immersed in a liquid thermosetting adhesive and then coated, a slot coating method in which a liquid thermosetting adhesive is dripped from a slot hole and coated on the steel plate, etc.
[0205] Besides these, a curtain coating method, a spray coating method using the principle of spraying to blow a liquid thermosetting adhesive onto a mist, an inkjet method, an electrodeposition coating method, or the like may be used.
[0206] [Heating, drying and curing process]
[0207] The heating and drying curing process is a process of heating a steel plate coated with a thermosetting adhesive and then cooling it to form a film of an adhesive resin composition on the surface of the steel plate. By heating, a part of the thermosetting resin in the thermosetting adhesive coated on the surface of the steel plate reacts with a part of the curing agent and cures, thereby forming a semi-cured product of the adhesive resin composition. In addition, when a thermosetting adhesive containing a solvent is used, by heating, a part of the thermosetting resin reacts with a part of the curing agent, and the solvent in the thermosetting adhesive evaporates to form a semi-cured product of the adhesive resin composition. In addition, a part of the curing agent does not dissolve during heating, or is recrystallized by cooling after heating. Thus, a film of an adhesive resin composition in which a specified amount of curing agent is dispersed in a crystalline state is formed.
[0208] (Heating method)
[0209] The heating (sintering) method may be a known heating and drying (sintering) method, which includes hot air drying, induction heating, infrared heating, vacuum heating, and the like.
[0210] The inventors of the present invention have conducted research and found that in order to set the area ratio of the curing agent crystals in the cross section of the adhesive resin composition film parallel to the surface of the steel plate within the above range, it is extremely important to control the heating (drying) conditions of the heating temperature (T) and the heating time. Specifically, it is necessary to control the heating temperature to a temperature T within the temperature range of 100 to 250°C, and to control the heating time to satisfy the following formula (i) according to the type of thermosetting adhesive used.
[0211] 0.8≦t / t0≦18.0···(i)
[0212] The meanings of the symbols in the above formula (i) are as follows.
[0213] t: Heating time in the heating drying and curing process
[0214] t0: The time required to form an adhesive resin composition film with a softening start temperature (Tss) of 50°C when drying a thermosetting adhesive at temperature T
[0215] By setting t / t0 to be greater than 0.8, the area ratio of the curing agent crystals can be set to less than 40%. In addition, by setting t / t0 to be less than 18.0, the area ratio of the curing agent crystals can be set to more than 0.10%. Here, the time t0 is determined as follows. That is, first, a thermosetting adhesive is applied to the surface of the steel plate. Then, heating is performed at a temperature T for various times, and the Tss of the adhesive resin composition film formed on the steel plate is measured by the aforementioned method. Then, based on the measurement results, the heating time required to set Tss=50°C at the heating temperature T is obtained, and it is set to t0.
[0216] (Cooling method)
[0217] The cooling method after heating the steel plate coated with the thermosetting adhesive can adopt a known cooling method, and any of air cooling, water cooling, mist cooling, and laminar cooling can be used in combination, or part of it can be used intermittently. The cooling rate is preferably 1 to 600°C / min. When the cooling rate is less than 1°C / min, the following situation exists: the curing reaction of the adhesive resin composition proceeds during cooling, and it is difficult to make a specified amount of curing agent crystals remain to form an adhesive resin composition film with a maximum needle penetration λ of less than 15%. On the other hand, when the cooling rate is higher than 600°C / min, the following situation exists: the cooling rate is not uniform depending on the location, and the thermal stress generated by the linear expansion coefficient of the steel plate and the adhesive resin is concentrated in the rapidly cooled location, and the magnetic properties of the steel plate are reduced.
[0218] <Preferred Production Method>
[0219] Furthermore, in order to set the area ratio of the curing agent crystals to 0.70 to 20% and more reliably ensure the anti-adhesive property and achieve the curing in a short time, it is preferred to set the Tg of the adhesive resin to 0.70 to 20%. uc The temperature is set to 30° C. or higher, the heating temperature in the heat drying and curing step is set to a temperature T within a temperature range of 100 to 190° C., and the heating time is controlled to satisfy the following formula (ii) according to the type of thermosetting adhesive used.
[0220] 1.3≦t / t0≦15.0···(ii)
[0221] In the above formula (ii), the meanings of the symbols are as follows.
[0222] t: Heating time in the heating drying and curing process
[0223] t0: The time required to form an adhesive resin composition film with a softening start temperature (Tss) of 50°C when drying a thermosetting adhesive at temperature T
[0224] When the softening start temperature Tss is set to 70°C or higher, t / t0 is preferably set to 2.0 or higher, and when the softening start temperature Tss is set to 70°C or higher, t / t0 is preferably set to 8.0 or lower. In addition, when the maximum penetration λ is set to 20% or higher, t / t0 is preferably set to 8.0 or lower.
[0225] <How to use>
[0226] (Storage method of adhesive resin composition coated electrical steel sheet)
[0227] The adhesive resin composition coated electromagnetic steel sheet of the present invention does not need to strictly manage temperature and humidity because the curing agent remains in the adhesive resin composition film in a crystalline state, and can be stored at room temperature and humidity. Moreover, even if it is transported by ship, it can prevent adhesion and adhesion, and can suppress the reduction of bonding performance. Therefore, it can be stored by a known steel plate storage method. Specifically, the adhesive resin composition coated electromagnetic steel sheet is coiled in a steel coil, or made into a cut plate and stacked, and packaged with paper or resin, or stored at room temperature and humidity without packaging. In the case of longer storage, it can also be stored at low temperature in a refrigerator or freezer.
[0228] <Manufacturing of Iron Core>
[0229] The adhesive resin composition coated electromagnetic steel sheet of the present invention can be used in the manufacture of an iron core. For example, the adhesive resin composition coated electromagnetic steel sheet of the present invention is punched or sheared, and after lamination, the laminate is hot-pressed to manufacture an iron core. In addition, the iron core is sometimes also called an adhesive iron core, a motor iron core, etc.
[0230] (Blanking and shearing method)
[0231] The processing and lamination can be performed by known punching and shearing methods. Specifically, the adhesive resin composition coated electromagnetic steel sheet is continuously conveyed into the mold from the adhesive resin coated electromagnetic steel sheet wound in the form of a steel coil. At this time, the processing oil is sprayed on the adhesive resin composition coated electromagnetic steel sheet before it is loaded into the mold. Then, while the adhesive resin composition coated electromagnetic steel sheet is conveyed into the mold, it is punched out multiple times in sequence into the desired shape, and shearing is performed when all the desired shapes are processed. Then, a method of dropping the sheared adhesive resin composition coated electromagnetic steel sheet into a receiving portion in the mold and laminating is cited.
[0232] (Thermocompression bonding)
[0233] The iron core composed of the stacked adhesive resin composition coated electromagnetic steel sheets can be pressurized and crimped in the mold, or the iron core composed of the stacked adhesive resin composition coated electromagnetic steel sheets can be extracted from the mold, loaded into a heating device and pressurized. Heating can be applied by a known heating method. Specifically, hot air heating using the heat flow of hot air in an oven, etc., resistance heating using resistive heating, low-frequency and high-frequency induction heating using induced power, infrared light heating such as near-infrared and far-infrared using radiant heat, etc. can be used. Among them, heating based on a near-infrared light heater is preferred. Based on the heating performed by a near-infrared light heater, the heater has a fast response speed, and can be heated at a high energy density, so that the iron core can be heated at a high speed. As a result, the curing of the semi-cured material of the adhesive resin composition constituting the adhesive resin composition film is almost not carried out, and it is relatively easy to heat the iron core to the curing temperature.
[0234] Hereinafter, the present invention will be described in further detail based on examples, but the present invention is not limited to the following examples within the scope of the gist of the present invention.
[0235] Example 1
[0236] <Test piece>
[0237] [Steel Plate]
[0238] A non-oriented electrical steel sheet having a thickness of 0.35 mm was used.
[0239] [Thermosetting adhesive]
[0240] The raw materials used in the thermosetting adhesive are shown in Table 1. The blending of the adhesive resin composition is shown in Table 2. The numerical values shown in Table 2 are the blending amounts (parts by mass) of the respective raw materials when the total amount of the epoxy resin is 100 parts by mass.
[0241] [Table 1]
[0242]
[0243] [Table 2]
[0244] Table 2
[0245]
[0246] <Preparation of adhesive resin composition and production of thermosetting adhesive>
[0247] The resin raw material, additive, curing agent, and curing accelerator were prepared in the composition shown in Table 2 to prepare an adhesive resin composition. Then, a solvent was added so that the solid content concentration in the liquid of the adhesive resin composition became 40% by mass, and the prepared liquid was stirred and mixed at room temperature for 3 hours to obtain a thermosetting adhesive. In addition, the numbers of the thermosetting adhesives shown in Tables 3 to 5 correspond to the numbers of the adhesive resin compositions shown in Table 2.
[0248] <Tg uc Determination of >
[0249] After casting the thermosetting adhesive onto the glass plate, it was placed in a dryer for 24 hours and dried under normal pressure. Thereafter, it was further vacuum dried at room temperature for 48 hours to remove the solvent. After vacuum drying, the extruded film was recovered from the glass plate and heated at 5°C / min using a differential scanning calorimeter: DSC (manufactured by Hitachi High-Tech Science Co., Ltd.) was used to measure the glass transition temperature Tg (midpoint glass transition temperature) when uncured according to JIS K7121:2012. The results are recorded in Table 2.
[0250] <Example 1>
[0251] <Manufacturing of Adhesive Resin Composition-Coated Electrical Steel Sheet>
[0252] After cleaning the surface of a 220×200 mm non-oriented electrical steel sheet with acetone, a thermosetting adhesive 1 was applied to the surface of the non-oriented electrical steel sheet (200×200 mm) using a roll coater (manufactured by FURNACE Co., Ltd.) in such a way that the film thickness after drying becomes 4.5 μm. After coating, it was dried at 140°C for 2.5 minutes to remove the solvent, thereby forming an adhesive resin composition film. And, after drying, cooling water was blown onto the surface of the steel sheet, and cooled to room temperature to obtain an adhesive resin composition coated electrical steel sheet. Here, the steel sheet temperature was measured by installing a thermocouple on the adhesive portion of the steel sheet surface.
[0253] <Examples 2 to 14>
[0254] Adhesive resin composition-coated electrical steel sheets were obtained in the same manner as in Example 1 except for the thermosetting adhesive and drying conditions shown in Tables 3 to 5.
[0255] <Measurement of the area ratio of curing agent crystals>
[0256] A polarizing filter (U-AN360-3 manufactured by OLYMPUS) is set on an orthogonal Nicol on an upright microscope (microscope manufactured by OLYMPUS: BX53M), and the cross section of the adhesive resin composition film covering the steel plate parallel to the surface of the steel plate is observed at 100 to 800 times. At this time, the magnification is appropriately selected within the above range according to the difficulty of identifying the crystal image of the curing agent. Thereafter, color photography is performed, the RGB tones are divided, only the G component is extracted, and binarization is performed using the image processing software in VHX5000 manufactured by KEYENCE. In this way, the area ratio of the bright phase is obtained. This operation is performed on three arbitrarily selected test bodies, and the average value is set as the area ratio.
[0257] Figures 2 to 10 Polarizing microscope images of Examples 1, 2, 5, 6, 7, 11, and 12 and Comparative Examples 2 and 3 described later are shown in Tables 3 to 6. Calculated area ratios of curing agent crystals are shown in Tables 3 to 6.
[0258] <Measurement of Tss, λ, and t0>
[0259] A test piece was cut from the dried adhesive resin composition coated electromagnetic steel plate and embedded in epoxy resin. After the epoxy resin was cured, it was ground to obtain a smooth cross section of the steel plate. The cross section of the steel plate was observed under a microscope to measure the thickness of the adhesive resin composition film. Furthermore, a 7×7 mm test piece was cut, and the adhesive-coated surface was set as the upper surface in a sample tube for the needle penetration mode of a thermomechanical analyzer (TMA, manufactured by Hitachi High-Tech Science Corporation), and heated from -50°C to 300°C at 5°C / min in the needle penetration mode. Then, the penetration length of the TMA probe into the adhesive resin composition film covering the surface of the steel plate was measured. Based on the data, Tss was obtained. In addition, based on the data, the maximum value of the needle penetration length was obtained and λ was calculated. The results are shown in Tables 3 to 5.
[0260] Furthermore, the electromagnetic steel sheet coated with a thermosetting adhesive on the surface so that the film thickness after drying becomes 4.5 μm was dried at 140°C for different drying times, and samples were prepared. The needle penetration length into the adhesive resin composition film was measured by TMA penetration mode under the same conditions, and the correlation between the drying time and Tss when drying at the temperature shown in Tables 3 to 5 was obtained. And based on this data, the time t0 at which Tss = 50°C of the adhesive resin composition film was determined. The results are shown in Tables 3 to 5.
[0261] <Adhesion and adhesion test>
[0262] Cut two pieces of 50×50mm of the dried adhesive resin composition coated electromagnetic steel plate, and stack them in such a way that the bonding surfaces overlap each other to become 40×50mm. Pressurize the stacked steel plates at 8MPa at 50°C for 30 minutes. After unloading the load, use a precision spring balance to measure the tensile shear bonding strength between the bonding surfaces, and evaluate it according to the following evaluation criteria. The greater the adhesion between the resin layers of the adhesive composition, the greater the tensile shear bonding strength. Therefore, the following points are used to evaluate the resistance to adhesion (with the order of A>B>C>D having a preventive effect). The measurement is carried out 5 times respectively.
[0263] A: 0.1 kPa or less, B: more than 0.1 kPa and less than 0.5 kPa, C: more than 0.5 kPa and less than 1 kPa, D: more than 1 kPa
[0264] <Adhesion and adhesion test>
[0265] Cut two pieces of 50×50mm of the dried adhesive resin composition-coated electromagnetic steel plate and stack them in such a way that the bonding surfaces overlap each other at 40×50mm. While pressurizing the stacked steel plates at 8MPa, put them in an oven (relative humidity 90%) set at a plate temperature of 50°C for 12 weeks. After 12 weeks, take out the stacked steel plates from the oven and unload the load. After unloading the load, use a precision spring balance to measure the tensile shear bonding strength between the bonding surfaces. If the bonding between the resin layers of the adhesive composition progresses during storage, the tensile shear bonding strength becomes larger. Therefore, the following review points are used to evaluate the resistance to bonding (with the order of A>B>C>D having a preventive effect). The measurements are performed 5 times each.
[0266] A: 0.1 kPa or less, B: more than 0.1 kPa and less than 0.5 kPa, C: more than 0.5 kPa and less than 1 kPa, D: more than 1 kPa
[0267] <Short-time curing in the thermocompression bonding process>
[0268] Cut two pieces of 100×25 mm of the dried adhesive resin composition coated electromagnetic steel plate, and stack them in such a way that the bonding surfaces overlap each other with a size of 25×25 mm. While pressurizing the stacked steel plates at 1 MPa, heat them to 200°C at 5°C / second, and keep them at 200°C for 1 minute. Then, cool them to room temperature, and measure the tensile shear bonding strength before storage (bonding strength after drying) according to JIS K 6850:1999. In addition, use the adhesive resin composition coated electromagnetic steel plate stored in an oven at 50°C×12 weeks (relative humidity 90%), and perform the same tensile shear bonding strength test to measure the tensile shear bonding strength after storage (bonding strength after storage). The measurements were performed 5 times each.
[0269] A: 10MPa or more, B: 5MPa or more but less than 10MPa, C: 1MPa or more but less than 5MPa, D: less than 1MPa
[0270] [Table 3]
[0271] Table 3
[0272]
[0273] [Table 4]
[0274] Table 4
[0275]
[0276] [Table 5]
[0277] Table 5
[0278]
[0279] <Comparative Examples 1 to 3>
[0280] An adhesive resin composition-coated electromagnetic steel sheet was obtained in the same manner as in Example 1 except that the thermosetting adhesive and drying conditions shown in Table 6 were used.
[0281] The obtained adhesive resin composition was used to coat the electrical steel sheet, and Tss, λ, and the area ratio of the curing agent crystals were measured in the same manner as in Examples 1 to 14. The adhesive adhesion test, adhesive adhesion test, and whether the composition could be cured in a short time in the thermocompression bonding process were evaluated.
[0282] [Table 6]
[0283] Table 6
[0284]
[0285] <Comparative Example 4>
[0286] According to Example 43 of Japanese Patent Publication No. 11-162724, a high molecular weight epoxy prepolymer (Mn=6000) was manufactured using a bisphenol A type epoxy resin (EPICOTE828 manufactured by Mitsubishi Chemical). Next, an acrylic resin composed of methacrylic acid, styrene, and ethyl acrylate was polymerized (mass ratio: 174 / 87 / 29). After 200 parts of the acrylic resin were dissolved in a solvent in 267 parts of the high molecular weight epoxy prepolymer, an amine catalyst (diethylaminoethanol) was added and stirred at 105°C for 3 hours. Then, deionized water was added over a period of 30 minutes to obtain an emulsion with a solid content of 25%. In this emulsion, 5 parts of phenolic resin (bisphenol A resol type phenolic resin) and 20 parts of DICY were added relative to the amount of resin in the emulsion of 100 to obtain an epoxy emulsion adhesive (thermosetting adhesive 6). Then, the thermosetting adhesive 6 was applied to the surface of the electromagnetic steel sheet using a bar coater, dried at 200° C. within the sheet temperature range described in paragraph 0057 of the patent publication for 10 minutes, and cooled to obtain an adhesive resin composition-coated electromagnetic steel sheet.
[0287] The obtained adhesive resin composition was used to coat the electromagnetic steel sheet, and Tss, λ, and the area ratio of the curing agent crystal were measured in the same manner as in Examples 1 to 14, and further evaluated whether the adhesive adhesion test and the ability to cure in a short time in the thermocompression bonding process were performed. As a result, the area ratio of the curing agent crystal was 0.00%, and the adhesive adhesion resistance and the adhesive strength after storage were D, similar to Comparative Examples 2 and 3.
[0288] <Results>
[0289] According to Examples 1 to 14, the electromagnetic steel sheet covered with an adhesive resin composition film composed of a semi-cured adhesive resin composition and in which the amount of curing agent crystals is controlled to a specified amount, suppresses adhesion and adhesion even when stored for a long time in a high-temperature and humid environment, and can be cured in a short time in the hot pressing process and exhibit adhesive strength.
[0290] On the other hand, according to Comparative Example 1, when the area ratio of the curing agent crystals deviates from the upper limit, sufficient bonding strength cannot be obtained even after drying and hot pressing. The presumed reason is that the curing agent crystals remain in the adhesive resin composition film even after hot pressing. According to Comparative Examples 2 to 4, when the amount of curing agent crystals deviates from the lower limit, bonding adhesion occurs during storage, and the bonding strength after storage is also reduced. The presumed reason is that the curing agent dissolved during drying undergoes a slow curing reaction during storage. In addition, according to Comparative Example 4, even if a known adhesive is used to manufacture by a known method, the adhesive resin composition-coated electromagnetic steel sheet of the present invention cannot be easily manufactured. Moreover, it is known that it is outside the scope of the constituent elements of the present invention, so bonding adhesion occurs during storage in the same way as Comparative Examples 2 and 3, and the bonding strength after storage is also reduced.
[0291] According to the comparison between Examples 1, 2, and 8 and other Examples, when the area ratio of the curing agent crystals is 30.00% or more, the adhesive strength after drying is slightly reduced. In addition, in Examples 1, 2, and 8, the adhesive strength after storage is also slightly reduced. It is inferred that this is because some curing agent crystals remain in the adhesive resin composition film after thermal compression bonding, which becomes a starting point, thereby reducing the strength and the adhesive strength.
[0292] Furthermore, according to the comparison between Examples 5, 10, 11, and 14 and other Examples, there is a tendency that the anti-adhesive property is slightly deteriorated when the area ratio of the curing agent crystals is 0.10 to 0.60%. This is presumed to be because the curing agent dissolved in the heating and drying curing step causes a slow curing reaction between the adhesive resin composition films to proceed during storage.
[0293] Furthermore, when comparing Examples 5 and 6, although Tss is the same, Example 6 is better than Example 5 in terms of anti-adhesive properties. This is presumed to be due to the following reasons. In Example 5, the Tg of the adhesive resin composition 2 used is uc Less than 30°C, on the other hand, in Example 6, the Tg of the adhesive resin composition 1 used is uc 30°C or more. As a result, in order to set Tss to 80°C in the heating and drying curing process, more heat input was put into Example 5. As a result, it is estimated that more curing agent was dissolved in the heating and drying curing process in Example 5. In fact, the area ratio of the curing agent crystals is also smaller in Example 5. Therefore, it is inferred that in Example 5 where the curing agent is more dissolved, the slow curing reaction is easy to proceed during storage, and the adhesion resistance is slightly deteriorated.
[0294] In addition, according to the comparison between Example 1 and Examples 2 to 4, 6, 7, 9, and 14, the adhesive resin composition coated electromagnetic steel sheet dried at 140°C for less than 1.1×t0 hours has poor resistance to adhesion. This is presumed to be because the adhesive resin composition is not sufficiently cured after drying. And, according to the comparison between Example 14 and Examples 2 to 4, 6, 7, and 9, the adhesive resin composition coated electromagnetic steel sheet dried at 140°C within 15.0×t0 hours has better resistance to adhesion. The presumed reason is that when drying exceeds 15.0×t0 hours, the dissolution of the curing agent crystals in the heating drying and curing process progresses, and the slow curing reaction caused by the curing agent dissolved during storage progresses.
[0295] Industrial Applicability
[0296] According to the present invention, an adhesive resin composition coated electromagnetic steel sheet is obtained, which can prevent adhesion and reduction of adhesive performance even if it is stored for a long time after the adhesive is applied and dried, and the adhesive resin composition film can be cured in a short time during hot pressing. Therefore, the adhesive resin film electromagnetic steel sheet of the present invention can be preferably used as a material for the iron core (stator, rotor, etc.) of motors of household appliances (air conditioners, vacuum cleaners, audio, etc.) and automobiles (HV, EV).
Claims
1. An adhesive resin composition coated electromagnetic steel sheet comprising a steel sheet and an adhesive resin composition coating film on at least one surface of the steel sheet, The adhesive resin composition film is a semi-cured product of an adhesive resin composition composed of a curing agent and an adhesive resin at least part of which contains a thermosetting resin. The maximum needle penetration λ of the adhesive resin composition film at 100 to 300° C. measured by thermomechanical analysis described in JIS K 7196:2012 is 3% or more and less than 100%, A part of the curing agent is present in the adhesive resin composition film in a crystalline state. The area ratio of the curing agent in a crystalline state in the cross section of the adhesive resin composition film parallel to the surface of the steel plate is 0.10 to 40%.
2. The adhesive resin composition coated electromagnetic steel sheet according to claim 1, The area ratio of the crystalline curing agent is 0.70 to 20%.
3. The adhesive resin composition coated electromagnetic steel sheet according to claim 1 or 2, The adhesive resin composition film has a softening start temperature Tss of 50° C. or higher as measured by thermomechanical analysis described in JIS K 7196:2012, and a maximum needle penetration λ of 15% or higher at 100 to 300° C.
4. The adhesive resin composition coated electromagnetic steel sheet according to any one of claims 1 to 3, The thermosetting resin includes at least one selected from epoxy resin, acrylic resin, urethane resin and unsaturated polyester resin.
5. The adhesive resin composition coated electromagnetic steel sheet according to any one of claims 1 to 4, The curing agent includes at least one selected from an amine curing agent, an amide curing agent, and an imidazole curing agent.
6. A method for producing an adhesive resin composition coated electromagnetic steel sheet, the method for producing an adhesive resin composition coated electromagnetic steel sheet according to any one of claims 1 to 4, comprising: A coating step of coating a liquid thermosetting adhesive including the adhesive resin and the curing agent on at least one surface of the steel plate; and The steel plate coated with the thermosetting adhesive is heated and then cooled to form a coating of the adhesive resin composition on the surface of the steel plate by heating and drying. The heating temperature in the heating drying and curing step is a temperature T in the temperature range of 100 to 250° C. The heating time in the heating drying and curing step satisfies the following formula (i): 0.8≦t / t0≦18.0···(i) in, The meanings of the symbols in the above formula (i) are as follows: t: heating time in the heating, drying and curing process, t0: time required to form an adhesive resin composition film having a softening start temperature of 50° C. when the thermosetting adhesive is dried at the temperature T.
7. The method for producing an adhesive resin composition-coated electromagnetic steel sheet according to claim 6, The glass transition temperature Tg of the adhesive resin uc Above 30℃, The heating temperature in the heating drying and curing step is a temperature T in the temperature range of 100 to 180° C. The heating time in the heating drying and curing step satisfies the following formula (ii): 1.3≦t / t0≦15.0···(ii) in, The meanings of the symbols in the above formula (ii) are as follows: t: heating time in the heating, drying and curing process, t0: time required to form an adhesive resin composition film having a softening start temperature of 50° C. when the thermosetting adhesive is dried at the temperature T.
8. The method for producing an adhesive resin composition-coated electromagnetic steel sheet according to claim 6 or 7, The adhesive resin contains 50% by mass or more of one or more thermosetting resins selected from epoxy resins, acrylic resins, urethane resins, and unsaturated polyester resins, based on the total amount of the adhesive resin.
9. The method for producing an adhesive resin composition-coated electromagnetic steel sheet according to any one of claims 6 to 8, The curing agent includes one or more selected from amine curing agents, amide curing agents, and imidazole curing agents.
Citation Information
Patent Citations
Production of surface-coated electrical steel plate for adhesion
JP1994182296A
Manufacture of electromagnetic steel plate for bonded iron core excellent in bonding strength, anticorrosion, and blocking resistance
JP1999162724A
Electromagnetic steel sheet with insulating film of good adhesion
JP2002260910A
Epoxy resin composition and processed product
JP2014152236A
Thermosetting epoxy resin composition
JP2017031268A